Ditiyeno[2,3-b;3 ,2 -d]tiyofen Ve Tiyeno[2,3-b]tiyofen Temelli Organik Elektronik Ve Optoelektronik Materyallerin Sentezleri Ve Özelliklerinin İncelenmesi - Taşkıran Çankaya, Şule (Fen Bilimleri Enstitüsü, 2014)
Ditiyenotiyofen türevli bileşikler elektronik ve optiksel alana giren elektrolümünesanlar, foton absorbanlar, flörosanlar, fotokronizm, optiksel kromoforlar, ince film transistorler, radar absorblayıcılar, iletken polimerler gibi önemli uygulama alanlarında kullanılmaktadır. Organik iletken teknolojisinde yakın zamanda büyük ilgi gören OLED “Organic Light Emitting Device” materyaller; genel olarak, bir alt tabaka “substrate”, anot, iletken tabaka, ışın yayıcı tabaka ve katotdan ibarettir. OLED materyalin bir parçası olan ışın yayıcı tabaka organik molekül ya da polimerler olabilmektedir. Bu aşamada ışın yayıcı tabakanın “band gap” karakteri büyük önem taşımaktadır ve materyal kimyasında düşük “band gap” değerine sahip ışın yayıcı tabakalar aranmakta ve tasarlanmaktadır. Bu çalışmada sentezlenen bileşikler, grubumuz tarafından geliştirilen tiyofenden yola çıkılarak oluşturulan 1-8-diketon tiyofen bileşiklerin LR (Lawesson Reaktanı) ve P4S10 ile reaksiyonundan elde edilmektedir. Ditiyenotiyofen “DTT” türevleri ditiyeno[3,2-b;2 ,3 -d]tiyofen, Ditiyeno[3,4-b;3 ,4 -d]tiyofen, Ditiyeno[2,3-b;3 ,4 -d]tiyofen, Ditiyeno[3,2-b;3 ,4 -d]tiyofen, Ditiyeno[2,3-b;2 ,3 -d]tiyofen, Ditiyeno[2,3-b;3 ,2 -d]tiyofen konjuge politiyofen sistemlerinde mevcut olan ve materyal kimyası açısından önemli olan elektrokimyasal ve optik özellikler göstermektedirler. DTT türevleri üç adet sülfür atomunu yapısında barındırmasından ileri gelen elektronca zengin ve ileri konjuge yapısından dolayı organik elektronik ve optoelektronik teknolojisinde, politiyofenlerde olduğu gibi geniş bir uygulama alanı bulurlar. Elektronca zengin ditiyenotiyofen (DTT) temelli bileşikler elektrolümünesanlar, foton absorbanlar, floresanlar, fotokromizm, optiksel kromoforlar, ince film transistörler, radar absorblayıcılar, iletken polimerler gibi önemli uygulama alanlarında kullanılabilmektedirler. Bu bilgiler ışığında iletken polimer teknolojisine katkı sağlamak amacıyla elektronca zengin, düşük bant aralıklı iletken polimerler oluşturmaya yatkın materyaller sentezlemek için grubumuzca geliştirilen 1,8-diketondan P4S10 ile halka kapama yöntemi temel alınarak sentezler yapıldı. Hedef Ditiyeno[2,3-b;3 ,2 -d]tiyofen türevlerine ulaşmak için 2,5-disübstitüe tiyofen, 1,8-diketon sentezi için kullanıldı. Sentezlenen 1,8-diketon türevi P4S10 ile halka kapama reaksiyonuna tabi tutularak DTT türevleri elde edildi. Türevlerin oksidasyon ve redüksiyon potansiyel ölçümlerini kapsayan çalışma döngülü voltmetre ile gerçekleştirilmiştir. Moleküllere ait floresans ölçümleri alınarak optoelektronik çalışmalar yapılmıştır. Türevlerin elektropolimerizasyon yöntemi ile polimerleştirme çalışmaları başarılı olmadı. Çalışmanın devamında türevlerinin spin yoğunlukları Gaussian 03 paket programı kullanılarak DFT metodu ile (PCM(ACN)-UB3LYP/6-311++G(d,p)//B3LYP/6-31+ G(d) ) de C2 simetrisi göz önüne alınarak hesaplandı. Sonuçlar tiyofen α-karbonunda spin yoğunluğu 0.20 olan fenil sübstütiye monomerinin elektropolimerizasyon için en iyi aday olduğunu göstermiştir. Bunun üzerine hesaplama çalışmaları geliştirilerek, fenil sübstitüye monomerin dimer molekülleri üzerine çalışmalar yapıldı ve spin yoğunluğu hesaplandı. Karbon atomları spin yoğunluğunun neredeyse sıfır olmasından dolayı dimer molekülleri daha fazla polimerizasyona uğramamaktadır sonucuna varıldı. Tiyenotiyofen (TT) türevleri iki adet sülfür atomunu yapısında barındırmasından ileri gelen elektronca zengin ve ileri konjuge yapısından dolayı organik elektronik ve optoelektronik teknolojisinde, ditiyenotiyofenler gibi geniş bir uygulama alanı bulurlar. Çalışma kapsamında tiyenotiyofen (TT) temelli bileşikler de sentezlendi. 2-bromotiyofenden yola çıkılarak elde edilen monoketonlardan 6- pozisyonlarında fenil ve parasübstitüefenil grubu içeren tiyeno[3,2-b]tiyofen türevleri elde edildi. Elektronik ve optoelektronik özellikleri incelenerek çalışma tamamlandı.

OLEDs “Organic Light Emitting Device”, which have recently attracted the attention of the research groups, in general, consist of a substurate, anode, conducting layer, emissive layer and a catode. Polyheteroaromatic compounds are important because of their availabilities in helding conjugated conductive polymers. Synthesis of materials or polymers with low band gaps and investigation of their properties are very popular today as in the recent past. As a consequence of having a long π-conjugation and a rigid, non-flexible structure, succesful results were obtained by introducing fused-thiophene ring systems in polymer backbone. These two important features results in low band gaps and high intramolecular interactions in solid films. The emissive layer which is a part of OLED material can be an organic molecule or a polymer having a long π-conjugation and a rigid, non-flexible structure, succesful results were obtained by introducing fused-thiophene ring systems in polymer backbone. The low band gap character of the emissive layer has a critical role. Therefore, there has been a great deal of search in material chemistry to obtain an emissive layer having low band gap value. With this technology, low-energy-powered flexible display screens and obtaining a lighter and smaller circuit elements is possible. Thus, the construction of space age technology products as stealth aircraft invisible to radar or low-energy-powered touchscreen smart windows are not science-fiction anymore. Beside the electronic properties, biological activities of some thienothiophenes were also examined and effectiveness on HIV, hepatitis B and some nervous system diseases are reported. Due to the above-mentioned features dithienothiophenes, thienothiophenes and conducting polymers derived from them are used in the design and construction of magnetic and photosensitive receptors, some sensors, electrochromic devices (ECD), organic ligth emitting diodes (OLED), field effect transistors (FET) which are basic componenets of electronic circuits, solar cells which directly transform electrical current into light (photovoltaic). By the development of technology it has been easier to synthesise and characterize new compounds with additonal groups attached to extend their usage. Also, improvement of the technology provided us to achieve devices with alternative configurations, as a result, effective and practical usage in daily life. Beyond other significant and applicable monomers, dthienothiophenes (DTT) are now being used extensively in many device techniques. Our group have been focused on a different synthetic procedure which concludes with extended conjugations. Electrochromic device applications, biosensors, photovoltaics and fluorescence biolabeling are some of the examples that these class of compounds can be used in. With all the information obtained by the literature research and the synthetic experience that we have focused on, some DTT and TT monomers have been synthesized and investigated in this thesis. Monomers were characterised by 1H-NMR, 13C-NMR, mass spectroscopy and their melting points were found. Their optic behaviours were examined. In the frame of the project, synthesis and investigation of the physical properties (CV, CV-UV, flourescence etc) of the highly conjugated dithienothiophene and thienothiophene based materials are planned. Dithienothiophenes (DTT) are formed by three fused thiophenes, which have six isomers, depending on the orientations of the thiophenes. They have been increasingly attractive due to their interesting properties in organic electronic materials. Presence of three sulfur atoms makes DTTs rich in electrons and good electron donor molecules, which are important properties for building blocks of wide variety of organic materials, having electronic and optical applications such as conducting polymers, electrochromic displays, electroluminescence, excited fluorescence, photochromism, nonlinear optical chromophores, transistors with high mobilities of on/off ratios, charge-transfer complexes and labeling for biological systems. Among the six isomers of DTT is the most studied one as the orientation of the fused three thiophene rings leads to a better conjugation. Considering its suitability for constructing π-conjugated systems, various synthetic methods have appeared in the literature including the method developed by our group, which led to the development of some interesting materials. It involves ring closure reactions of thiophenes containing 3-mono or 3,4-diketones to form thiophenes or dithiins with the use of Lawesson’s reagent (11) or phosphorus decasulfide (P4S10). In this study, as a continuation of our research line, the ring closure reaction was performed on thiophene containing 2,5-diketone to obtain 3,4-diaryldithieno[2,3-b;3_,2_-d]thiophenes (DTT) 2. Synthesis of Dithienothiophene functionalized with different substituents are carried out with the reaction of 1,8-diketon ring closure with P4S10, which is the pathway developed by our research group. Treatment of 2,5-dibromothiophene with two moles of n-BuLi at−78◦Cwas followed by addition of two moles of elemental sufur and then two moles of desired α-bromoketone to obtain the corresponding 2,5-diketones. The ring closure reaction of diketones was performed using P4S10 in refluxing toluene to obtain the DTTs monomers between 10% and 16%. It is important to note that when an impure P4S10 was used no product was obtained. The easiest way of identifying pure and impure P4S10 is that while the impure P4S10 has yellow color and bad smell, the pure one has very light yellow color and almost none or very slight smell. However, the lower yields of the DTTs is not related to the purity of P4S10, as the same P4S10 was used for the syntheses of the DTTs (dithieno[2,3-b;2_,3_-d]thiophenes), which gave higher yields up to 95%. It is known that carbons 3- and 4- of a thiophene ring are less nucleophile compare with the carbons 2- and 5-, which could be the possible explanation for the lower yields of the ring closure reactions of diketons. The oxidation reduction behaviors of the DTT monomers were investigated by cyclic voltammetry (CV). The voltammograms were recorded in acetonitrile/tetrabutylammonium hexafluorophosphate (0.1 M) solvent-electrolyte couple, using a CV cell consisting of Pt wire as working and counter electrodes andAg/AgCl as a reference electrode. Solutions were prepared as 1 × 10−3 M, monomer concentrations and the experiments were conducted at room temperature. The monomers DTT, having R groups “H,” “MeO,” “Br” and “NO2,” respectively, displayed oxidation potentials between 1.19 and 1.70V. Regarding the nature of the “R” groups on the phenyl moiety, the oxidation potentials followed the order of NO2 substutied DTT monomer (1.70V)> Br substutied DTT monomer (1.51V)> H substutied DTT monomer (1.47V)> MeO substutied DTT monomer (1.19 V). While NO2 substutied DTT monomer having strong electron withdrawing nitro group had the highest oxidation potential, the MeO substutied DTT monomer having strong electron donating methoxy group had the lowest oxidation potential. As a next step, their electropolymerizations were attempted. However, in spite of all the efforts, including different scan rates, altering the solvent-electrolyte couple, applying constant potential, etc., it was not successful. Rather than obtaining an increase at wave intensities of the CV curves, a decrease was obtained. In order to understand the behaviors of the monomers during the electropolymerization, a computational study was conducted. Many efforts were spent for the electropolymerization of DTT monomers. Although the studies using different scan rates or altering the solvent-electrolyte couple, neither with CV nor by applying constant potential, electropolymerization of DTT monomers couldn t be achieved. Computational calculations displayed positive radical spin densities at C2 positions for DTTs and almost zero for dimers. Results were proved that the steric hindrance and the negative spin densities at C2 positions of the dimer prevent electropolymerization. Summury, 3,4-Diaryl substituted DTT were synthesized, applying the diketone ring closure reaction, using P4S10. All attempts for their electrochemical polymerizations were failed. Computational chemistry studies revealed that although the DTTs had enough spin densities for electropolymerization at carbon 2- of the peripheral thiophenes, their dimers had spin densities less than zero, which prevented further chain elongation leading to their polymers. Same procedures were conducted for 3,4-dibromothiophene to achieve thieno[2,3-b]thiophenes containing bromine at 3-position and para-substituted phenyl ring on 6-position. Similiar to DTT prosedure, ring closure from monoketothiophene gives thienothiophene fused ring. 2-bromothiophene was lithiated with n-buthyllithium, treated with elemental sulfur than reacted with 2-bromoacetophenone and its derivatives containing methoxy, nitro and bromo substituents on the para-position of the phenyl ring. Obtained monoketothiophenes were reacted with P4S10 to give thieno[2,3-b]thiophenes with phenyl ring (para-H, MeO, NO2, Br) on 6-position. OLEDs “Organic Light Emitting Device”, which have recently attracted the attention of the research groups, in general, consist of a substurate, anode, conducting layer, emissive layer and a catode. Polyheteroaromatic compounds are important because of their availabilities in helding conjugated conductive polymers. Synthesis of materials or polymers with low band gaps and investigation of their properties are very popular today as in the recent past. As a consequence of having a long π-conjugation and a rigid, non-flexible structure, succesful results were obtained by introducing fused-thiophene ring systems in polymer backbone. These two important features results in low band gaps and high intramolecular interactions in solid films. The emissive layer which is a part of OLED material can be an organic molecule or a polymer having a long π-conjugation and a rigid, non-flexible structure, succesful results were obtained by introducing fused-thiophene ring systems in polymer backbone. The low band gap character of the emissive layer has a critical role. Therefore, there has been a great deal of search in material chemistry to obtain an emissive layer having low band gap value. With this technology, low-energy-powered flexible display screens and obtaining a lighter and smaller circuit elements is possible. Thus, the construction of space age technology products as stealth aircraft invisible to radar or low-energy-powered touchscreen smart windows are not science-fiction anymore. Beside the electronic properties, biological activities of some thienothiophenes were also examined and effectiveness on HIV, hepatitis B and some nervous system diseases are reported. Due to the above-mentioned features dithienothiophenes, thienothiophenes and conducting polymers derived from them are used in the design and construction of magnetic and photosensitive receptors, some sensors, electrochromic devices (ECD), organic ligth emitting diodes (OLED), field effect transistors (FET) which are basic componenets of electronic circuits, solar cells which directly transform electrical current into light (photovoltaic). By the development of technology it has been easier to synthesise and characterize new compounds with additonal groups attached to extend their usage. Also, improvement of the technology provided us to achieve devices with alternative configurations, as a result, effective and practical usage in daily life. Beyond other significant and applicable monomers, dthienothiophenes (DTT) are now being used extensively in many device techniques. Our group have been focused on a different synthetic procedure which concludes with extended conjugations. Electrochromic device applications, biosensors, photovoltaics and fluorescence biolabeling are some of the examples that these class of compounds can be used in. With all the information obtained by the literature research and the synthetic experience that we have focused on, some DTT and TT monomers have been synthesized and investigated in this thesis. Monomers were characterised by 1H-NMR, 13C-NMR, mass spectroscopy and their melting points were found. Their optic behaviours were examined. In the frame of the project, synthesis and investigation of the physical properties (CV, CV-UV, flourescence etc) of the highly conjugated dithienothiophene and thienothiophene based materials are planned. Dithienothiophenes (DTT) are formed by three fused thiophenes, which have six isomers, depending on the orientations of the thiophenes. They have been increasingly attractive due to their interesting properties in organic electronic materials. Presence of three sulfur atoms makes DTTs rich in electrons and good electron donor molecules, which are important properties for building blocks of wide variety of organic materials, having electronic and optical applications such as conducting polymers, electrochromic displays, electroluminescence, excited fluorescence, photochromism, nonlinear optical chromophores, transistors with high mobilities of on/off ratios, charge-transfer complexes and labeling for biological systems. Among the six isomers of DTT is the most studied one as the orientation of the fused three thiophene rings leads to a better conjugation. Considering its suitability for constructing π-conjugated systems, various synthetic methods have appeared in the literature including the method developed by our group, which led to the development of some interesting materials. It involves ring closure reactions of thiophenes containing 3-mono or 3,4-diketones to form thiophenes or dithiins with the use of Lawesson’s reagent (11) or phosphorus decasulfide (P4S10). In this study, as a continuation of our research line, the ring closure reaction was performed on thiophene containing 2,5-diketone to obtain 3,4-diaryldithieno[2,3-b;3_,2_-d]thiophenes (DTT) 2. Synthesis of Dithienothiophene functionalized with different substituents are carried out with the reaction of 1,8-diketon ring closure with P4S10, which is the pathway developed by our research group. Treatment of 2,5-dibromothiophene with two moles of n-BuLi at−78◦Cwas followed by addition of two moles of elemental sufur and then two moles of desired α-bromoketone to obtain the corresponding 2,5-diketones. The ring closure reaction of diketones was performed using P4S10 in refluxing toluene to obtain the DTTs monomers between 10% and 16%. It is important to note that when an impure P4S10 was used no product was obtained. The easiest way of identifying pure and impure P4S10 is that while the impure P4S10 has yellow color and bad smell, the pure one has very light yellow color and almost none or very slight smell. However, the lower yields of the DTTs is not related to the purity of P4S10, as the same P4S10 was used for the syntheses of the DTTs (dithieno[2,3-b;2_,3_-d]thiophenes), which gave higher yields up to 95%. It is known that carbons 3- and 4- of a thiophene ring are less nucleophile compare with the carbons 2- and 5-, which could be the possible explanation for the lower yields of the ring closure reactions of diketons. The oxidation reduction behaviors of the DTT monomers were investigated by cyclic voltammetry (CV). The voltammograms were recorded in acetonitrile/tetrabutylammonium hexafluorophosphate (0.1 M) solvent-electrolyte couple, using a CV cell consisting of Pt wire as working and counter electrodes andAg/AgCl as a reference electrode. Solutions were prepared as 1 × 10−3 M, monomer concentrations and the experiments were conducted at room temperature. The monomers DTT, having R groups “H,” “MeO,” “Br” and “NO2,” respectively, displayed oxidation potentials between 1.19 and 1.70V. Regarding the nature of the “R” groups on the phenyl moiety, the oxidation potentials followed the order of NO2 substutied DTT monomer (1.70V)> Br substutied DTT monomer (1.51V)> H substutied DTT monomer (1.47V)> MeO substutied DTT monomer (1.19 V). While NO2 substutied DTT monomer having strong electron withdrawing nitro group had the highest oxidation potential, the MeO substutied DTT monomer having strong electron donating methoxy group had the lowest oxidation potential. As a next step, their electropolymerizations were attempted. However, in spite of all the efforts, including different scan rates, altering the solvent-electrolyte couple, applying constant potential, etc., it was not successful. Rather than obtaining an increase at wave intensities of the CV curves, a decrease was obtained. In order to understand the behaviors of the monomers during the electropolymerization, a computational study was conducted. Many efforts were spent for the electropolymerization of DTT monomers. Although the studies using different scan rates or altering the solvent-electrolyte couple, neither with CV nor by applying constant potential, electropolymerization of DTT monomers couldn t be achieved. Computational calculations displayed positive radical spin densities at C2 positions for DTTs and almost zero for dimers. Results were proved that the steric hindrance and the negative spin densities at C2 positions of the dimer prevent electropolymerization. Summury, 3,4-Diaryl substituted DTT were synthesized, applying the diketone ring closure reaction, using P4S10. All attempts for their electrochemical polymerizations were failed. Computational chemistry studies revealed that although the DTTs had enough spin densities for electropolymerization at carbon 2- of the peripheral thiophenes, their dimers had spin densities less than zero, which prevented further chain elongation leading to their polymers. Same procedures were conducted for 3,4-dibromothiophene to achieve thieno[2,3-b]thiophenes containing bromine at 3-position and para-substituted phenyl ring on 6-position. Similiar to DTT prosedure, ring closure from monoketothiophene gives thienothiophene fused ring. 2-bromothiophene was lithiated with n-buthyllithium, treated with elemental sulfur than reacted with 2-bromoacetophenone and its derivatives containing methoxy, nitro and bromo substituents on the para-position of the phenyl ring. Obtained monoketothiophenes were reacted with P4S10 to give thieno[2,3-b]thiophenes with phenyl ring (para-H, MeO, NO2, Br) on 6-position.
Preparation And Investigation Of The Properties Of Electro And Optoelectro Active Materials Based On Dithieno[2,3-b;3 ,2 -d]thiophene And Thieno[2,3-b]thiophene
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2014
Thesis (PhD) -- İstanbul Technical University, Institute of Science and Technology, 2014
Keywords: OLED; DTT; TT; tiyofen; OLED; DTT; TT; Thiophene